Higher Education Policy Change in Europe: Academic Research Funding and the Impact Agenda. Issue 4 (1st October 2016) - Gunn, Andrew; Mintrom, Michael
Abstract : In the policy period following the Lisbon Strategy of 2000, European governments increasingly regard universities, and the research they produce, as key to enhancing economic performance. With this heightened respect for the value of university-based research, comes an impatience to see returns on the public investments made. We analyze how policy is being used to influence the academic research process through the evaluations and funding allocation that accompany public funding. This paper features examples from the European Union and recent policy developments in two nation states to investigate how policy seeks to enhance the non-academic impacts of academic research.